Dynamic project planning with digital twin - Zahno, Silvan; Corre, Jérôme; Petrovic, Darko; Mottiez, Gilles; Fracheboud, Loïc; Amand, Axel; Devènes, Steve; Maître, Gilbert; Carrino, Francesco (Frontiers in Manufacturing Technology, 2023)
The Digital Twin (DT) concept plays a crucial role in Industry 4.0 and the digitalization of manufacturing processes. A DT is a virtual representation of a physical object, system, or process, designed to accurately reflect its real-world counterpart. In manufacturing, existing process data is often incomplete and does not qualify as a DT. However, with the help of specialized communication frameworks and cheaper, easier-to-use sensors, it is possible to integrate the existing Manufacturing Execution System (MES) and Enterprise Resource Planning (ERP) data with the missing data gathered from the shopfloor to create a comprehensive DT. In this paper, we present a digital shopfloor Decision Support System (DSS) for non-linear aluminum manufacturing production. The system is split into five main components: digitization of shopfloor orders, merging and sorting of MES, ERP, and shopfloor data, custom and genetic optimization algorithms for the aging furnace production step, layout construction mechanism for optimal placement and stacking of orders in the furnace, and a user-friendly Graphical User Interface (GUI). The system's performance was evaluated through three tests. The first test measured the efficiency of digitization, the second aimed to quantify time saved in finding packets in the hall, and the last test measured the impact of the optimizer on furnace productivity. The results revealed a 23.5% improvement in furnace capacity, but limitations were identified due to usability and human intervention.